BRIGHT Kids : English activities book for kids / Anastasia Arum Sari...[et al] ; editor, Flora Maharani ; ilustrator, Denny Praja Ariandhy - Anastasia Arum Sari; Denny Praja Ariandhy; Flora Maharani (Kanisius, 2015)
... jilid : ilus. ; 29 cm [9 eks]